Rancang Bangun Pengusir Hama Burung dan Belalang Pada Padi Menggunakan Gelombang Ultrasonik Berbasis Lora - Wardani, Ayusta Lukita; Amirul Haq Al Rasyid (Elposys: Jurnal Sistem Kelistrikan, 2024)
Indonesia, as an agricultural country, faces the challenge of pests in the agricultural sector, one of which is the sparrow that often attacks rice plants, causing a decrease in rice yields. The use of traditional methods such as canned sound is considered less effective, so ultrasonic technology is chosen as a safer alternative to pesticides that can cause side effects to the environment. This research aims to design and test a sparrow and locust pest repellent tool on rice plants using ultrasonic waves based on LoRa technology, with the hope of offering a more efficient and environmentally friendly solution. Tests were conducted to determine the effectiveness of ultrasonic frequencies against sparrow and locust pests, as well as the maximum distance the tool can work. The device was tested with various wave frequencies (30 kHz, 35 kHz, 40 kHz) at different distances, and the LoRa communication range was measured until the signal was lost. The test results show that the optimal frequency to repel sparrows and locusts is 40 kHz with an effective range of up to 3 meters, and the LoRa module is able to transmit signals up to a distance of 63 meters. This research offers an alternative solution for farmers to repel pests effectively without harmful chemicals, as well as providing ease of tool control in areas without internet connection.